Factors Affecting The Attitude Of Mothers Towards Baby Massage In Mancon Village - Herdian Fitria Widyanto Putri; Atik Farokah; Qatrunnada Naqiyyah Khusmitha (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Baby massage is a popular therapy that has been carried out for a long time, both in Indonesia and around the world. Baby massage improves the baby's sleep and quality, relaxes the baby, improves the baby's eating, and has many other benefits. The implementation of baby massage is influenced by various factors, such as parental factors, environment, and others. This study aims to determine the factors that influence the mother's attitude toward massaging her baby. This study is an analytical observational with a cross-sectional design. The sample used had 22 respondents. The research was conducted on December 12, 2022, in Mancon Village, Wilangan, Nganjuk. Fisher's exact test is used for data analysis. The results showed that there was a correlation between motivation and the mother's attitude toward massaging her baby (p = 0.032). These results are inversely proportional to the mother's education and knowledge that do not correlate with the mother's attitude toward massaging her baby (p=0.842; p=0.255). It can be concluded that motivation strongly and significantly influences the mother's attitude toward massaging her baby.